2021
DOI: 10.3389/fonc.2021.667920
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-Mediated Clearance of Free Genomic DNA in the Cytoplasm Protects the Growth and Survival of Cancer Cells

Abstract: The cGAS (GMP-AMP synthase)-mediated senescence-associated secretory phenotype (SASP) and DNA-induced autophagy (DNA autophagy) have been extensively investigated in recent years. However, cGAS-mediated autophagy has not been elucidated in cancer cells. The described investigation revealed that active DNA autophagy but not SASP activity could be detected in the BT-549 breast cancer cell line with high micronucleus (MN) formation. DNA autophagy was identified as selective autophagy of free genomic DNA in the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…As assumed, the silencing of cGAS led to decreased cells proliferation, migration, and increased apoptosis in AGS and MKN45 cells. Previously, it has been reported that silencing cGAS decrease the viability of BT-549 cells [34]; furthermore, our xenograft experiment in BALB/nu mice also demonstrated a decrease in tumor growth in sh-cGAS MKN45 cells. To explore how cGAS exert the proliferation of GC cells, we performed GO and KEGG functional enrichment analysis, which showed its involvement in DNA replication and repair.…”
Section: Discussionsupporting
confidence: 80%
“…As assumed, the silencing of cGAS led to decreased cells proliferation, migration, and increased apoptosis in AGS and MKN45 cells. Previously, it has been reported that silencing cGAS decrease the viability of BT-549 cells [34]; furthermore, our xenograft experiment in BALB/nu mice also demonstrated a decrease in tumor growth in sh-cGAS MKN45 cells. To explore how cGAS exert the proliferation of GC cells, we performed GO and KEGG functional enrichment analysis, which showed its involvement in DNA replication and repair.…”
Section: Discussionsupporting
confidence: 80%
“…Nevertheless, the progression of cancers is a complicated process, collectively determined by various factors that are interactively fabricated in cancer cells and tumour microenvironments. More interestingly, our recent investigation revealed that cGAS-STING could be activated in severe DNA damage; however, SASP activity has been shown to alternatively mediate DNA autophagy in protecting cancer cell survival [37]. In fact, STAT6 expression is also positively and negatively involved in cancer progression [38].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the cellular senescent phenotype is inhibited by H-151 treatment. 25 , 33 A recent study showed that systemic H-151 administration can alleviate inflammatory diseases, including acute kidney injury, 34 neuron loss, and neurologic disability in amyotrophic lateral sclerosis model mice. 21 These data suggested that H-151 is a promising therapeutic agent for inflammatory disorders.…”
Section: Discussionmentioning
confidence: 99%